"I see the future": Associations between innovation and resources in the case of an exporting Western Australian regional family firm. Issue 3 (5th September 2016) - Duarte Alonso, Abel; Austin, Ian Patrick
Abstract : Purpose: The purpose of this paper is to investigate the associations between the resources of a Western Australian regional family firm exporting to Asia and innovation through the lens of the theory of innovation and the resource-based view (RBV) of the firm. Design/methodology/approach: In-depth, un-structured telephone and face-to-face interviews were conducted with five members of the firm, including the co-owner. A visit to the business facilities complemented the data collection process. Findings: The importance of tangible and intangible resources, such as forward thinking or investments in technologies, human capital and research is clearly illustrated; these resources positively influence innovative practices. Associations between the findings and the theoretical frameworks were identified. For instance, the imperfectly imitable and non-substitutable attributes comply with the RBV of the firm, and the hypothesised four dimensions of innovation. Importantly, the significance of strategic partnering emerges as an extension of these attributes. Originality/value: This study addresses some knowledge gaps, first, contributing to the body of research on family firms' adoption of innovation. In addition, the study contributes to the literature on regional Western Australian family firms operating internationally. This state makes a significant contribution to Australia's economy, and its close geographic proximity to various important consumer markets highlights future opportunities for family firms in international trade. Despite such potential, research on global family firms operating in this state has been almost non-existent.